Greater effects of high- compared with moderate-intensity interval training on cardio-metabolic variables, blood leptin concentration and ratings of perceived exertion in obese adolescent females - Racil, G; Coquart, JB; Elmontassar, W; Haddad, M; Goebel, R; Chaouachi, A; Amri, M; Chamari, K (Biology of Sport, 2016)
This study examined the effects of high- vs. moderate-intensity interval training on cardiovascular fitness, leptin levels and ratings of perceived exertion (RPE) in obese female adolescents. Forty-seven participants were randomly assigned to one of three groups receiving either a 1:1 ratio of 15 s of effort comprising moderate-intensity interval training (MIIT at 80% maximal aerobic speed: MAS) or high-intensity interval training (HIIT at 100% MAS), with matched 15 s recovery at 50% MAS, thrice weekly, or a no-training control group. The HIIT and MIIT groups showed improved (p˂0.05) body mass (BM), BMI Z-score, and percentage of body fat (%BF). Only the HIIT group showed decreased waist circumference (WC) (p=0.017). The effect of exercise on maximal oxygen uptake (VO2max) was significant (p=0.019, ES=0.48 and p=0.010, ES=0.57, HIIT and MIIT, respectively). The decrease of rate-pressure product (RPP) (p<0.05, ES=0.53 and ES=0.46, HIIT and MIIT, respectively) followed the positive changes in resting heart rate and blood pressures. Blood glucose, insulin level and the homeostasis model assessment index for insulin decreased (p<0.05) in both training groups. Significant decreases occurred in blood leptin (p=0.021, ES=0.67 and p=0.011, ES=0.73) and in RPE (p=0.001, ES=0.76 and p=0.017, ES=0.57) in HIIT and MIIT, respectively. In the post-intervention period, blood leptin was strongly associated with %BF (p<0.001) and VO2max (p<0.01) in the HIIT and MIIT groups, respectively, while RPE was strongly associated with BM (p<0.01) in the HIIT group. The results suggest that high-intensity interval training may produce more positive effects on health determinants in comparison with the same training mode at a moderate intensity.